Assessing students approaches to learning using a matrix framework in a Malaysian public university - Teoh, Hee Chong; Abdullah, Maria Chong; Roslan, Samsilah; Mohd Daud, Shaffe (Springer, 2014)
This study aims to evaluate the learning characteristics of students using a matrix framework of learning approaches (MFLA) in a Malaysian public university. A survey form based on Biggs’s study process questionnaire (SPQ) was distributed to a total of 350 students. This study employed a descriptive correlation research design to address the research objectives. The findings revealed that Malaysian students are prone to applying the achieving approach in their studies. The achieving approach is the most preferable learning characteristic. The results also indicated that four of the nine hypothetical learning approaches exist, two of which are positive in nature. As a result, a proposed teaching method based on the MFLA was introduced to suit the needs of these major learning characteristics among students.